Microwave-Assisted Cyclocondensation for the Synthesis of 3-Aryl-2-thioquinazolin-4(3H)-ones - Patil, Suresh; Jadhav, S.D.; Shejwal, R.V.; Deshmukh, M.B. (Asian Journal of Chemistry, 2011)
An efficient synthesis of 3-aryl-2-thioquinazolin-4(3H)-one 1a-f is given by the condensation of anthranilic acid and dithiocarbamate triethylammonium salts of substituted aniline in ethanol as solvent under microwave irradiation.